Modelling the informal sector and energy consumption in Ghana - John Bosco Dramani; Prince Boakye Frimpong; Kwame Ansere Ofori-Mensah (Social Sciences and Humanities Open, 2022)
The International Monetary Fund (2017) defines the informal sector as unrecorded economic activities that possess monetary value and contribute to tax revenue and gross domestic product. This sector accounts for a huge percentage of economic activity in sub-Saharan Africa and given the numerous regulations on the formal sector it may grow further. Since the activities of the informal sector are unrecorded, how does its energy demand affect national energy demand? In answering this question, we rely on the autoregressive distributed lag estimation technique to quantify the effect of the informal sector on energy consumption. We find that the informal sector exerts a 0.055% adverse effect on energy consumption. Further, we find that education, employment, and foreign direct investment are channels through which the informal sector affects energy consumption. The findings have relevant policy implications. First, since the growth of the informal sector decreases energy consumption, the economies of developing countries should be formalized to spur industrial energy consumption. Second, the national energy policies of Ghana and other developing countries should take into consideration the characteristics of the informal sector in conducting projections of energy demand.